2016
DOI: 10.1177/0963947016652782
|View full text |Cite
|
Sign up to set email alerts
|

Commonplacing the public domain: Reading the classics socially on the Kindle

Abstract: Amazon leads the market in ebooks with the Kindle brand, which encompasses a range of dedicated e-reader devices and a large ebook store. Kindle users are able to share the experience of reading ebooks purchased from Amazon by selecting passages of text for upload to the Kindle Popular Highlights website. In this article, I propose that the Kindle Popular Highlights database contains evidence that readers are re-appropriating commonplacing -the act of selecting important passages from a text and recording them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…related to suspense, curiosity, or surprise effects [109]. This is in line with one of the main functions of highlighting, as shown by Rowberry [110] on a corpus of Kindle Popular Highlights: users highlight pivotal narrative moments. However, in highly commented paragraphs there is no trace of the commonplaces identified by Rowberry: moral values do not spark many discussions among Wattpad readers, although this might be due to genre-specific limitations of our corpus or to the readers' young age.…”
Section: Engagementsupporting
confidence: 72%
See 1 more Smart Citation
“…related to suspense, curiosity, or surprise effects [109]. This is in line with one of the main functions of highlighting, as shown by Rowberry [110] on a corpus of Kindle Popular Highlights: users highlight pivotal narrative moments. However, in highly commented paragraphs there is no trace of the commonplaces identified by Rowberry: moral values do not spark many discussions among Wattpad readers, although this might be due to genre-specific limitations of our corpus or to the readers' young age.…”
Section: Engagementsupporting
confidence: 72%
“…For Classics, it is interesting to note that commenting on Wattpad is different than highlighting on a Kindle e-readers. In the latter case, Rowberry [110] has shown that readers focus on "perceived wisdom" and "affective climaxes of a narrative". We have shown that the most commented paragraphs on Wattpad display more basic narrative effects-suspense, curiosity and surprise-not necessarily related to emotionally intense scenes.…”
Section: Emotionsmentioning
confidence: 99%
“…It shows that Internet affects reading. For the discussion, the readers can "share the quotation" (Rowberry, 2016) or "construct narrative or argument". In Indonesia, a research that was conducted by Son et al (2011) reports that Indonesian teachers' computer literacy and typing skills level are adequate or higher.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author predicts that this will increase e-book acceptance rate in India. Rowberry 75 observed that the Kindle Popular Highlights database contains evidence that readers are re-appropriating common placing i.e. the act of selecting important passages from a text and recording them in a separate location for later re-use, while reading public domain titles on the Kindle.…”
Section: E-books Formats and Reading Devicesmentioning
confidence: 99%